Cytoplasmic innate immune sensors - Masters, Seth (Henry Stewart Talks, 2019)
Introduction to the Adaptive vs. Innate Immune system, Autoimmunity vs. Autoinflammatory disease, Cytoplasmic innate immune sensors, NLRs and the inflammasome, NLRP3 inflammasome, Pyrin inflammasome, NLRC4 inflammasome, NLRP1 inflammasome, NOD1 and NOD2, RLRs and detection of cytoplasmic RNA/DNA, DNA sensing by cGAS and AIM2, RNA sensing by Rig-I and MDA-5, Programmed inflammatory cell death, Spreading the signal (cGAMP and Inflammasomes), PAMPs, DAMPs and HAMPs